Pengaruh Naungan Terhadap Pertumbuhan Embrio Penyu Lekang (Lepidochelysolivacea) Di Lhok Pante Tibang Syiah Kuala, Banda Aceh - Fitri Rianda; Widya Sari; Muhammadar Muhammadar (Universitas Syiah Kuala, 2017)
ABSTRACTThis is a study of the influence of shade on the growth of the olive ridley turtle’s embryo (Lepidochelys olivacea) in Lhok Pante Tibang, Syiah Kuala Banda Aceh with the purpose of getting an overview about the influence of shade and incubation period to the stages of growth of olive ridley turtle’s embryo. Sampling was done in Lhok Pante Tibang, Syiah Kuala Subdistrict Banda Aceh in January-April of 2016. This research uses the Complete Random Disposition (Rancangan Acak Lengkap), the factorial were of 2 factors of treatment, shade treatment and incubation period. Shade treatment consisted of semi-naturalopen nests with 70% of paranet shade. Incubation period consisted of the incubation of 5, 10, 20 and 40 days, every combination of treatment consisted of five repetitions (five eggs). The parameters measured covered the diameter of the egg, the egg weight, the length of the embryo, the weight of the embryo, temperature, rate of water sand and the intensity of the light. The research’s data result were analyzed by Analysis of Variant (ANOVA), and then followed by a Tukey test. The results of the research showed that there are olive ridley turtle’s eggs which were fertilized and not fertilized by doing the shade treatment and incubation period. Environmental factor that were measured is the average value of the rate of water in shaded nest 3 ± 1 % no shade 4 ± 3, the temperature of the air was 29,66 ± 4,24 oC, the temperature of the shaded soil 30,71 ± 6,45 oC, with no shade 33,52 ± 2,20 oC, the intensity of the light at 06.00 WIB with shade 90 ± 85,24 no shade 74,2 ± 44, the intensity of the light at 14.00 WIB with no shade 32385,71 ± 2542,59, no shade 64371,43 ± 34055,28. The condition of the beach where the turtle laid eggs had a big influence on the growth of olive ridley turtle’s embryo.Keywords : Olive Ridley Turtle (Lepidochelys olivacea), Embryo, Lhok Pante Tibang. ABSTRAKKajian tentang pengaruh naungan terhadap pertumbuhan embrio penyu lekang (Lepidochelys olivacea) di Lhok Pante Tibang Syiah Kuala, Banda Aceh, ditujukan untuk mendapatkan gambaran mengenai pengaruh naungan dan periode inkubasi terhadap tahapan pertumbuhan embrio penyu lekang. Pengambilan sampel dilakukan di Lhok Pante Tibang, Kecamatan Syiah Kuala Banda Aceh pada bulan Januari-April 2016. Penelitian ini menggunakan Rancangan Acak Lengkap (RAL), faktorial 2 faktor perlakuan, perlakuan naungan dan periode inkubasi. Perlakuan naungan terdiri atas sarang semi alami terbuka dan bernaungan jaring paranet 70%. Perlakuan periode inkubasi terdiri atas inkubasi 5, 10, 20 dan 40 hari, tiap kombinasi perlakuan terdiri dari lima ulangan (lima butir telur). Parameter yang diukur meliputi diameter telur, berat telur, panjang embrio, berat embrio, suhu, kadar air pasir dan intensitas cahaya. Data hasil penelitian dianalisis dengan Analisis of Varian (ANOVA), yang dilanjutkan dengan uji Tukey. Hasil penelitian menunjukkan terdapat telur penyu lekang yang terbuahi dan tidak terbuahi perlakuan naungan dan periode inkubasi. Faktor lingkungan yang diukur adalah rata-rata nilai kadar air sarang bernaungan 3 ± 1 % tidak ada naungan 4 ± 3, Suhu udara 29,66 ± 4,24oC, suhu tanah ada naungan 30,71 ± 6,45 oC, tidak ada naungan 33,52 ± 2,20 oC, intensitas cahaya ada naungan pukul 06.00 WIB 90 ± 85,24 tidak ada naungan 74,2 ± 44, intensitas cahaya pukul 14.00 WIB ada naungan 32385,71 ± 2542,59 tidak ada naungan 64371,43 ± 34055,28. Kondisi pantai peneluran penyu sangat mempengaruhi terhadap perkembangan embrio penyu lekang.Kata Kunci : Penyu Lekang (Lepidochelys olivacea), Embrio, Lhok Pante Tibang.